Feasibility Analysis and Strategies of Anchovy Business Development: Economic Resilience Analysis - Hardianti Hardianti; Syaiful Anwar; Ahmad Rizani (Government & Resilience, 2024)
This study aimed to determine the feasibility analysis and strategies used in the development of anchovy business in Tarakan City. This type of research is descriptive research using quantitative and qualitative approaches. The population and sample in this study were the Usaha Kembang Turi and this study used primary data. Based on the results of this study it is found that financial feasibility was seen from the R/C ratio of 2.40, BCR (Benefit Rate of Return) of 1.40, FRR (Financial Rate of Return) of 65.11%, PPC (Payback Period of Capital) of 1.54 and BEP (Break Even Point) of basic unit price were 118 units and the basic price of the sales was Rp.2, 340,000. Based on the predetermined eligibility criteria, it could be said that the anchovy business in Tarakan City is feasible to operate. The analysis phase was carried out by looking at the internal and external conditions of the company using situation analysis or SWOT analysis through IFAS (Internal Strategic Factors Analysis Summary), EFAS (External Strategic Factors Analysis Analysis), SWOT diagrams, and SWOT matrices. The results of data analysis showed that the strategies used were the SO strategies (Strength-Opportunity).